Longitudinal assessment of liver stiffness and risk factors for advanced fibrosis in adolescents with metabolic dysfunction-associated steatotic liver disease: a retrospective observational study - Cao, Wenshu; Feng, Congcong; Ye, Jizhong; Zhou, Jianfeng; Wang, Lin; Lian, Yanling (Frontiers in Medicine, 2025)
BackgroundThe global incidence of metabolic dysfunction-associated steatotic liver disease (MASLD) in adolescents is steadily increasing. This research aims to characterize adolescents diagnosed with MASLD clinically and evaluate their long-term outcomes in community and tertiary medical centers located in Shanghai. Furthermore, the investigation assesses the diagnostic efficacy of vibration-controlled transient elastography (VCTE) among adolescents with MASLD.MethodsWe retrospectively analyzed data from adolescent patients (10–18 years) diagnosed with MASLD referred to Shanghai hospitals during the period 2019–2023. Diagnostic criteria included sustained alanine transaminase elevations exceeding twice the upper normal threshold or radiological confirmation of hepatic steatosis, following exclusion of alternative etiologies. VCTE-derived liver stiffness measurements (LSMs) were classified as normal (≤7.0 kPa, F0-F1), significant fibrosis (7.1–9.0 kPa, F2), and advanced fibrosis (≥9.1 kPa, F3-F4), to distinguish fibrosis severity.ResultsA total of 140 adolescents were enrolled (67.9% male), with an average age of 13.8 years. Dyslipidemia was common (48.6%; n = 68), followed by impaired glucose tolerance or diabetes (27.1%; n = 38) and hypertension (21.4%; n = 30). Following a mean follow-up duration of 2.1 years, remission of MASLD occurred in only 8.6% of patients (n = 12). Among the 50 patients evaluated by VCTE, 22 (44%) exhibited normal LSM values, whereas significant fibrosis and advanced fibrosis were suspected in 11 (22%) and 17 (34%) individuals, respectively. Independent risk factors significantly associated with advanced fibrosis included age ≥16 years (OR, 7.18), presence of IGT/DM (OR, 10.16), and elevated aspartate aminotransferase levels exceeding 70 U/L (OR, 17.33).ConclusionThere is a rapid increase in adolescent MASLD incidence in Shanghai. According to LSM assessments, adolescents diagnosed with MASLD may have heightened risks of advanced hepatic fibrosis as they approach late adolescence.